Educational Research Squared (ER²), a methodology that combines the study and practice of social work. - Herrera-Pastor, David (My University, 2024)
This contribution derives from the research entitled: "Learning from the margins. Social inclusion of highly marginalised youth in urban settings" (2019-1-DK01-KA203-060285), funded by the EU (https://erasmus-plus.ec.europa.eu/projects/search/details/2019-1-DK01-KA203-060285). The aim was to learn from the reality experienced by young people in situations of exclusion in order to provide social and educational responses conducive to their inclusion. The project was articulated according to what is called Educational Research Squared (ER²), which is a methodology that combines the study with the practice of social work. The educational dimension is elevated to the second power because, in addition to researching a pedagogical-social issue, this process is implemented in an educational way. To this end, this project combines the lifeline, as the main data collection technique, and socio-educational accompaniment, as an intervention model. The aim of this contribution is to analyse the potential of this methodology. A priori, young people were not particularly interested in participating in the project. In order to try to involve them and make the process pedagogical, a socio-educational accompaniment (Herrera, Padilla and González-Monteagudo, 2020) was implemented, supported by volunteer university students, of the same age as the young people. Creating a social circle of interest and inclusiveness. The results show the benefits of the methodology and how complementary the combination of its primary instruments was. If only the former had been used, the process would have been cold and the young people would probably not have participated, or would have done so superficially, which would have yielded data of the same nature. But by establishing authentic personal relationships (Herrera, Juárez & Ruiz-Román, 2020), a fundamental bond was built for young people to open up and tell their lives to people they trusted.
Keywords: Trabajo social - Metodología; Educational research squared; Childhood, adolescence and youth at social risk; Social work; Lifeline; Socio-educational accompaniment